MANAJEMEN PENGELOLAAN SURAT MASUK DAN SURAT KELUAR DIDINAS LINGKUNGAN HIDUP KABUPATEN BANTUL DIY - Dian Vita Sari; Suliantoro, Suliantoro (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
This research aims to determine whether the management steps for managing incoming and outgoing letters at the Bantul Regency Environmental Service are good enough, the steps are: Incoming letters are received, recording is carried out (controlling incoming letters and agenda books), data is entered ( provide disposition sheets and control cards), disposed of to the head of service, distributed to the section receiving the disposition, followed up and archived. For the steps for outgoing letters, letters that have been processed by the management unit are sent to the head of the service to request a signature. If the letter has been sent down from the head of the service, they are asked for the classification number and date, affixed with a stamp, a copy is taken to be archived, put in an envelope with an address, handed over to the officer for the delivery process. The obstacles to the management of incoming and outgoing letters at the Bantul Regency Environmental Service are letters arriving outside working hours, lack of human resources for managing outgoing letters and urgent letters that arrive suddenly.